(untitled) (Computer systems and information technologies, 2022)
Were considered the issues of making managerial decisions in uncertain conditions with classical criteria approach for estimation of alternatives from a set of possible decision-making variants. Was considered the decision-making model in uncertain conditions, based on the game theory concept when the uncertain situation was caused by objective circumstances which are unknown or have casual nature. Was formalized the optimal decision-making process on the conditions for adjusting the inventories use volume. Were considered the concepts and components of the information situation. Was considered the information situation classifier related to environmental uncertainty and applicable classical criteria in the decision-making process. The risk function in the implementation of a particular strategy is defined. Found risk magnitude for a possible information situation and the recorded state of the environment. Defined risk as the difference between the solution when accurate data on the environment state is available and the result when data on the state of the environment is not determined. Three-month plan creation for inventory use is taken as an example, were considered alternative strategies for the formation of inventories. Developed plan adjustment algorithm for enterprise production stocks. Defined an effective production strategy for the next strategic management of enterprise production stocks period according to the algorithm. An assessment matrix of the considered information situation is formed. According to estimates, an alternative solution was chosen. Using the voting method, the optimal strategy and the amount of risk were found. It is concluded that it is insufficient to use one classical criterion for optimal decision-making in uncertain conditions.